ANALYSIS KI-KD MADRASAH IBTIDAYAH OF DIMENSIONAL HOTS IN KMA No. 165 OF 2014 MORAL LESSONS - Ayu Munira (As-Sibyan, 2020)
This study aims to look at KI-KD at the Ibtidayah Madrasah level. In this study KI-KD will be analyzed which leads to the dimension of HOTS in KMA Number 165 of 2014 on moral lessons. The hope will be able to map where the Basic Competencies are HOTS and are still LOTS. That way will make it easier for teachers to achieve learning targets. This study aims to look at the KI-KD that leads to the dimensions of HOTS in KMA Number 165 of 2014 on akidah akhlak lessons. The hopes will be able to map the Basic Competencies that have been HOTS and are still LOTS. This research is library research. The data are descriptive-qualitative, obtained from primary sources KMA No.165 of 2014. The technique of collecting data through documentation techniques and analyzed by descriptive method and content analysis method. The results of the analysis show that Basic Competence (KD) made by the government is still dominated at the cognitive level C1 (remembering). Then followed by C2 (understanding) and C3 (applying). While C5 (evaluating) and C6 (creating) don't exist at all. With KD LOTS as much as C1; 53, C2; 45, C3; 25, and the number of KD HOTS as much as C4;2, C5; 0, C6; 0.